2016
DOI: 10.1111/josh.12439
|View full text |Cite
|
Sign up to set email alerts
|

Verbal Bullying Changes Among Students Following an Educational Intervention Using the Integrated Model for Behavior Change

Abstract: The study findings indicate that a school-based intervention can positively impact on verbal bullying experiences and behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 47 publications
0
12
0
2
Order By: Relevance
“…Conversely, some studies showed a significant relationship between students' knowledge and the rate of aggression. 56,57 Given the comparison of teachers’ knowledge scores of parents and students and their level of education toward two groups, teachers lacked a high level of knowledge toward the types of aggression. Similar to our study, various studies suggested that most teachers lacked a clear understanding of the definition of expression.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, some studies showed a significant relationship between students' knowledge and the rate of aggression. 56,57 Given the comparison of teachers’ knowledge scores of parents and students and their level of education toward two groups, teachers lacked a high level of knowledge toward the types of aggression. Similar to our study, various studies suggested that most teachers lacked a clear understanding of the definition of expression.…”
Section: Discussionmentioning
confidence: 99%
“…Behavioral intention is determined not only by individual's attitude toward the behavior but also by individual's subjective evaluation of the social norms. Social norms and awareness of bullying at the school and community levels are associated with bullying experience and behaviors among students . If students think that the school environment does not encourage defending behaviors, they are less likely to act when witnessing a bullying incident.…”
Section: Discussionmentioning
confidence: 99%
“…Social norms and awareness of bullying at the school and community levels are associated with bullying experience and behaviors among students. 37,38 If students think that the school environment does not encourage defending behaviors, they are less likely to act when witnessing a bullying incident. It takes longer to form a new norm in the school.…”
Section: Discussionmentioning
confidence: 99%
“…Em Espanha, num estudo com 176 adolescentes, foi avaliado um programa antibullying composto por várias técnicas, dentre as quais a dramatização/interpretação de papéis, e identificaram que, após a intervenção, houve redução da agressão física e verbal entre os estudantes (Garaigordobil & Martínez-Valderrey, 2016 incorporadas numa intervenção educativa realizada com estudantes da 10ª série escolar, equivalente ao 1º ano do ensino secundário. Os resultados indicaram diminuição na frequência de agressão direta (verbal) após a intervenção (Naido, Satorius, Vries, & Taylor, 2016). Na Califórnia, pesquisadores realizaram uma intervenção de prevenção ao bullying por meio de histórias infantis e interpretação de papéis (role-playing), e os resultados semelhantes aos do presente estudo, apontando redução na média de vitimização de 1,76 para 1,60, no GI e aumento de 1,23 para 1,38, no GC (Wang & Goldberg, 2017).…”
Section: Discussionunclassified